Embracing Solitude: Women and New Monasticism. By Bernadette Flanagan - Reynolds, Stefan D. (The journal of theological studies, 2014)
Bernadette Flanagan is Director of Research at All Hallows College in Dublin City University, where, with others, she has pioneered the study of Christian spirituality particularly from the perspective of contemporary situations. Her approach is dialogical. Her first book, Spirit in the City: Voices from Dublin's Liberties (Dublin: Veritas, 1999) combined a preparatory apparatus for the study of spirituality with reports of interviews from Dublin inner-city dwellers. In her new book, Embracing Solitude, she presents women who through the centuries from the Desert Mothers to today have pioneered and lived out new models of female spirituality.